PERSEPSI MASYARAKAT PADA PROGRAM YUK KEEP SMILE (YKS) DI TRANS TV (STUDI DI KEL. TELUK BELITUNG KEC. MERBAU KAB. KEPULAUAN MERANTI) - Azrul Fahmi; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The program  Fast video television of course there is a process transmission greetings from communicator to audiensnya. Message through the program Fast or television show  its inherent value contained value/, the  values that television station as an effective communicator tried to can convey to audience or komunikannya. Various kinds of program presented by television stations. They compete to present can program  is interesting and liked by many people. One of the mushrooming in Indonesia this program is Fast  -  Let's keep Smile (YKS) in Trans TV.  This research uses qualitative tried to understand and interpret the meaning of an event interaction appearance man in certain situations in the perspectives researchers itself. Technical  data collection  in a way observation, interview and documentation. Data that was recieved by then processed for reduced, served to produce a general conclusions. Informant in this research method  12  person based on  snowbal  sampling. While for the investigation validity  data  therefore use techniques for the extended the inclusion and triangulation.Results of these studies  showing a public perception on the performance Fast YKS in  Trans TV according to informers interesting and different with entertainment events that are on  television stations such as Pesbuker in  ANTV  and Extravaganza in Trans 7, and YKS willing to accept criticism and suggestions from other people to improve the motivating and Fast YKS  since launching until this time less comfort, and the social control in the event this can be seen from the performance of the players who are  less influence over children.Keyword : Persepsi Masyarakat, YKS, Program Televisi